2011
DOI: 10.1103/physrevb.83.195419
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic effect of near-surface alloying on hydrogen interaction on the aluminum surface

Abstract: A small amount of catalyst, such as Ti, was found to greatly improve the kinetics of hydrogen reactions in the prototypical hydrogen storage compound NaAlH4. We propose a near-surface alloying mechanism for the rehydrogenation cycle based on detailed analysis of available experimental data as well as first-principles calculations. The calculated results indicate that the catalyst remains at subsurface sites near the Al surface, reducing the dissociation energy barrier of H2. The binding between Ti and Al modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…8(c), while the Ti species are always detected from the EDS spectra of three samples (not shown here). So we believe that nanocrystalline TiO 2 and/or amorphous phase TieAl clusters, as the active species for NaAlH 4 , remain at the subsurface sites of the surface due to binding between Ti and Al near the Al surface, reducing the dissociation energy barrier of H 2 , which is agreement with the theory calculation results [33].…”
Section: 3supporting
confidence: 74%
“…8(c), while the Ti species are always detected from the EDS spectra of three samples (not shown here). So we believe that nanocrystalline TiO 2 and/or amorphous phase TieAl clusters, as the active species for NaAlH 4 , remain at the subsurface sites of the surface due to binding between Ti and Al near the Al surface, reducing the dissociation energy barrier of H 2 , which is agreement with the theory calculation results [33].…”
Section: 3supporting
confidence: 74%
“…Many processes could impair the kinetic rates, such as nucleation, defect diffusion, and H 2 dissociation and diffusion at surfaces. Previous theoretical studies demonstrated that computational methods can be applied in the study of kinetic process for various hydrogen storage systems [26][27][28][29][30][31][32][33][34][35][36]), and some systems (such as AlH 3 and MgH 2 ) were reported to have undesired H 2 dissociation barriers which may hinder the reaction process [26][27][28][29][37][38][39]. Thus, as an initial stage to examine the kinetic process for MgB 2 hydrogenation and find out the possible rate limiting processes, we studied hydrogen dissociation and diffusion on MgB 2 surface in this work (and hydrogen diffusion in bulk MgB 2 in a separate paper [40]).…”
mentioning
confidence: 99%
“…Wang et al remind us, in favor of this role of subsurface Ti, that metallic aluminum does not absorb diatomic hydrogen from the gas phase by itself. Meanwhile, atomic hydrogen strongly reacts with aluminum surfaces to form alanes [142]. Thus, subsurface Ti would promote H 2 dissociation and enhance H mobility and adsorption [142].…”
Section: The “Single Metal” Alanatesmentioning
confidence: 99%
“…Meanwhile, atomic hydrogen strongly reacts with aluminum surfaces to form alanes [142]. Thus, subsurface Ti would promote H 2 dissociation and enhance H mobility and adsorption [142]. These effects constitute essentially the “hydrogen pump” action mechanism that was proposed for Ti [134].…”
Section: The “Single Metal” Alanatesmentioning
confidence: 99%